2019
DOI: 10.18552/2019/idscmt5064
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable utilization of biopolymers and biocement in aggregation of granular materials

Abstract: Soil stabilisation through materials such as lime or cement have considerable environmental penalty due to high embodied energy of the cementitious material. Biogeotechnology allows cement formation with dramatically reduced carbon footprint and promises a sustainable soil improvement method. In the current study, investigations were performed to evaluate the effect of biopolymer Xanthan gum and Microbially Induced Calcite Precipitation (MICP) on cementation of sands as well as sand-clay mixtures individually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The images also revealed the presence of clay mixture, which could be the result of mixing the plant gum polysaccharide into the soil particles, which is said to increase the surface strength and stability of the particles (Figure 11). Similar results were observed in a study conducted by Ramachandran et al [56]. The EDX analysis revealed the elemental composition present in the soil, which correlated with the soil analysis report (Figure 12).…”
Section: Soil Qualitysupporting
confidence: 90%
See 1 more Smart Citation
“…The images also revealed the presence of clay mixture, which could be the result of mixing the plant gum polysaccharide into the soil particles, which is said to increase the surface strength and stability of the particles (Figure 11). Similar results were observed in a study conducted by Ramachandran et al [56]. The EDX analysis revealed the elemental composition present in the soil, which correlated with the soil analysis report (Figure 12).…”
Section: Soil Qualitysupporting
confidence: 90%
“…The addition of polymers such as xanthan and cellulose to the soil reduced the rate of soil erosion by 80% [79]. Microscopic investigation of sand mixed with xanthan gum polysaccharide revealed biopolymer bridging between pores and the formation of biopolymer clay matrix [56]. Likewise, in another study, strong bonding between the void gaps of dispersive soils were observed after the addition of xanthan gum [80].…”
Section: Discussionmentioning
confidence: 99%